Molecular Liver Cancer Prevention in Cirrhosis by Organ Transcriptome Analysis and Lysophosphatidic Acid Pathway Inhibition - Nakagawa, Shigeki; Wei, Lan; Song, Won Min; Higashi, Takaaki; Ghoshal, Sarani; Kim, Rosa S.; Bian, C. Billie; Yamada, Suguru; Sun, Xiaochen; Venkatesh, Anu; Goossens, Nicolas; Bain, Gretchen; et al. (Cancer cell, 2016)
Cirrhosis is a milieu that develops hepatocellular carcinoma (HCC), the second most lethal cancer worldwide. HCC prediction and prevention in cirrhosis are key unmet medical needs. Here we have established an HCC risk gene signature applicable to all major HCC etiologies: hepatitis B/C, alcohol, and non-alcoholic steatohepatitis. A transcriptome meta-analysis of >500 human cirrhotics revealed global regulatory gene modules driving HCC risk and the lysophosphatidic acid pathway as a central chemoprevention target. Pharmacological inhibition of the pathway in vivo reduced tumors and reversed the gene signature, which was verified in organotypic ex vivo culture of patient-derived fibrotic liver tissues. These results demonstrate the utility of clinical organ transcriptome to enable a strategy, namely, reverse-engineering precision cancer prevention. [Display omitted] •Clinically applicable pan-etiology HCC risk biomarker was established•Global transcriptome map of cirrhosis identified HCC chemoprevention targets•Global transcriptome map of cirrhosis identified clinically relevant animal models•LPA pathway inhibitors were verified as HCC chemopreventive and anti-fibrotic drugs Nakagawa et al. establish a hepatocellular carcinoma (HCC) risk gene signature applicable to all major HCC etiologies and identify the lysophosphatidic acid pathway as a central chemoprevention target, pharmacological inhibition of which reduces tumors and reverses the gene signature in preclinical models.